2010
DOI: 10.1007/s10562-010-0368-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Succinic Acid to γ-Butyrolactone over Palladium Catalyst Supported on Mesoporous Alumina Xerogel

Abstract: Mesoporous alumina xerogel (AX) was prepared by a sol-gel method for use as a support for palladium catalyst. Palladium catalyst supported on mesoporous alumina xerogel (Pd/AX) was then prepared by an impregnation method. For comparison, commercial alumina (AC) was also used to prepare Pd/AC catalyst by an impregnation method. Liquid-phase hydrogenation of succinic acid to c-butyrolactone (GBL) was carried out using supported palladium catalysts (Pd/AC and Pd/AX). The supported palladium catalysts (Pd/AC and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…We found that alumina prepared by a sol-gel method retained hydroxyl-rich surface, leading to the unique chemical and physical properties compared to that prepared by a conventional method. For this reason, Pd/AX catalyst showed excellent reusability and stability in the hydrogenation of SA to GBL, as reported in our previous work [9]. However, Pd/AX catalyst prepared by an impregnation method required a number of calcination and drying steps, and palladium particles were not uniformly dispersed on alumina.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…We found that alumina prepared by a sol-gel method retained hydroxyl-rich surface, leading to the unique chemical and physical properties compared to that prepared by a conventional method. For this reason, Pd/AX catalyst showed excellent reusability and stability in the hydrogenation of SA to GBL, as reported in our previous work [9]. However, Pd/AX catalyst prepared by an impregnation method required a number of calcination and drying steps, and palladium particles were not uniformly dispersed on alumina.…”
Section: Introductionsupporting
confidence: 59%
“…Succinic anhydride (SAN) was also produced as an intermediate compound in the hydrogenation of succinic acid to GBL. Except for Pd-A950 catalyst, all the Pd-A catalysts showed higher yield for GBL than Pd/AX catalyst (yield for GBL = 53%) which was prepared by an impregnation method in our previous work [9]. This result indicates that Pd-A catalyst prepared by a single-step sol-gel method served as a more efficient catalyst than Pd/AX catalyst prepared by an impregnation method.…”
Section: Hydrogenation Of Succinic Acid (Sa) To Gbl Over Pd-a Catalystmentioning
confidence: 70%
See 1 more Smart Citation
“…[3,4] SUC has aw ider ange of industrial applications. [8][9][10][11][12][13] Bi-metallicR e ÀRu catalysts showed selectivityt oB DO at 200 8C under 80 bar in dioxane. In particular, BDO, which was until recently manufactured entirely from petroleumbased feedstocks, is an important commodity chemical that is used to manufacture large amounts of plastics and important polymers such as polyesters,p olyurethanes,a nd spandex elastic fibers.Avariety of catalysts have been described extensively in patents for the catalytic hydrogenation reaction of maleic acid, maleic anhydride, and SUC to BDO.…”
Section: Introductionmentioning
confidence: 95%
“…[3][4][5] However, these petrochemical-based feedstocks have economical and environmental problems. 6 Therefore, demand for finding a cheap and clean feedstock for the production of BDO has continuously increased.…”
Section: Introductionmentioning
confidence: 99%